Studi Kasus Laki-laki 38 Tahun dengan Priapismus Iskemik Ideopatik Intermiten - Ahmad Fauzan; Wendy Susri (Lembaga Pengembangan Kinerja Dosen, 2025)
Priapism is a urological emergency that can cause permanent disability so it requires fast and precise treatment by a doctor, we recently treated a man with intermittent idiopathic ischemic priapism with oral gabapentin 300 mg and dutasteride 0.5 mg, Before we decided on pharmacological therapy as an effort to prevent recurrent episodes of erection, we had planned invasive therapy as a first-line therapy option, namely aspiration, irrigation, inter cavernosal therapy with winter procedure, but before we had time to do the procedure the penis had detumescence so we canceled the procedure considering that massive bleeding occurred and there was no clinical benefit if the procedure was continued, the treatment immediately showed results after administration with a decrease in the frequency and duration of erections. In the second week the patient came back to our hospital emergency room, we planned the same action winter procedure but before we could do it the penis had detumescence, we gave additional pharmacological therapy Dutasteride 1x0.5 mg, After giving a combination of gabapentin and dutasteride for 2 weeks and we noted no reports of recurrent erectile episodes after and after stopping the drugs there were no reports of recurrent erectile episodes. Gabapentin and Dutasteride may be the main safe choice for the management of intermittent idiopathic ischemic priapism.